1978
DOI: 10.1104/pp.62.5.761
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ribosomal RNA Accumulation by Auxin in Artichoke Tissue

Abstract: Artichoke ( Heianthus tuberosus L.) tuber tissue cultured in the presence of the auxin 2,4-dichlorophenoxyacetic acid accumulates ribosomal RNA at a rate of 0.135 micrograms per hour per explant whereas there is little accumulation in nontreated tissue. The addition of auxin enhanced the transcription of the 2.5 x 106 precursor 3.5-fold and increased the rate of processing 1.8-fold. The major effect of auxin, however, was a vast increase in the rate of processing of the 1.39 x 106 precursor to the 1.3 x 106 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Thus, in agreement with other plants in which the 2.8 to 3.4 megadalton component is apparently missing (e.g. 15,17,18), the processing of cytoplasmic rRNA involves a primary transcript of2.5 megadalton and intermediates of 1.4, 1.0, and 0.75 megadalton (17).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Thus, in agreement with other plants in which the 2.8 to 3.4 megadalton component is apparently missing (e.g. 15,17,18), the processing of cytoplasmic rRNA involves a primary transcript of2.5 megadalton and intermediates of 1.4, 1.0, and 0.75 megadalton (17).…”
Section: Resultssupporting
confidence: 52%
“…the same prerRNA half-life) in dark-grown and irradiated tissue. It is interesting to note that, in a related study dealing with the influence of THIEN ANE auxin on the labeling kinetics of precursor and mature RNAs in artichoke tissue (15), a discrepancy between the hormone-mediated increases of pre-rRNA pool size and the accumulation rate of mature rRNAs has been found. This result has been taken as evidence that the switching on of rRNA accumulation in this tissue is in part due to an increase in transcription of pre-rRNA and in part due to posttranscriptional control involving changes in the kinetics of processing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All rights reserved. Key, 1983), the accumulation of rRNA (Melanson, 1978), and the phosphorylation of certain ribosomal proteins (Pérez et al, 1987(Pérez et al, , 1990. Auxin also caused an increase in the coordinated expression of ribosomal proteins (Gantt and Key, 1985;Gao et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Since mature rRNAs (1 8S and 25S or 0.7 and 1.3 x 106 D, respectively) are initially transcribed as a large precursor molecule of about 2.8 x 105 D in some plants (8,17,25) and about 2.3 x 106 in others (6, 28) including soybean (15), the rate of processing of these large transcripts could be involved in establishing the rate of accumulation of new ribosomes. Melanson and Ingle (23) in fact have reported that precursor processing, including a large increase in the rate of processing of the 1.4 x 106 precursor into the mature 1.3 x 106 (25S) rRNA, accounts for a part of the auxin-enhanced synthesis and accumulaton of ribosomes in artichoke tissue. The availability of ribosomal proteins may also play a role in the rate of processing of pre-rRNA and/or accumulation of ribosomes.…”
Section: Discussionmentioning
confidence: 99%